Pulsar scintillation studies with LOFAR: II. Dual-frequency scattering study of PSR J0826+2637 with LOFAR and NenuFAR. Issue 4 (9th February 2023) - Wu, Ziwei; Coles, William A; Verbiest, Joris P W; Ambalappat, Krishnakumar Moochickal; Tiburzi, Caterina; Grießmeier, Jean-Mathias; Main, Robert A; Liu, Yulan; Kramer, Michael; Wucknitz, Olaf; Porayko, Nataliya; Osłowski, Stefan; et al.
ABSTRACT: Interstellar scattering (ISS) of radio pulsar emission can be used as a probe of the ionized interstellar medium (IISM) and causes corruptions in pulsar timing experiments. Two types of ISS phenomena (intensity scintillation and pulse broadening) are caused by electron density fluctuations on small scales (< 0.01 au). Theory predicts that these are related, and both have been widely employed to study the properties of the IISM. Larger scales (∼1 – 100 au) cause measurable changes in dispersion and these can be correlated with ISS observations to estimate the fluctuation spectrum over a very wide scale range. IISM measurements can often be modelled by a homogeneous power-law spatial spectrum of electron density with the Kolmogorov (−11/3) spectral exponent. Here, we aim to test the validity of using the Kolmogorov exponent with PSR J0826+2637. We do so using observations of intensity scintillation, pulse broadening and dispersion variations across a wide fractional bandwidth (20–180 MHz). We present that the frequency dependence of the intensity scintillation in the high-frequency band matches the expectations of a Kolmogorov spectral exponent, but the pulse broadening in the low-frequency band does not change as rapidly as predicted with this assumption. We show that this behaviour is due to an inhomogeneity in the scattering region, specifically that the scattering is dominated by a region of transverse size ∼40 au. The power spectrum of the electron density, however, maintains the Kolmogorov spectral exponent from spatial scales of 5 × 10 −6  au to ∼100 au.